Global self-esteem and self-efficacy correlates: Relation of academic achievement and self-esteem among Emirati students - Afari, E.; Ward, G.; Khine, Myint Swe (2012)
We investigated the relationships between global self-esteem, academic self-efficacy and academic performance among a sample of 255 college students in the United Arab Emirates. The widely used Rosenberg’s Self-Esteem Scale (RSES; Rosenberg, 1965) and an academic self-efficacy scale, modified from (Jinks and Morgan, 1999) were used to assess student’s self-esteem and their academic self-efficacy. Each student’s average grade for the mid-semester and final semester was used as the performance measure. Confirmatory factor analyses using Analysis of Moment Structures (AMOS) version 18 performed on the scores of the RSES revealed two factors (positive and negative self-esteem) as hypothesized. Correlated results indicated significant relationships between global self-esteem and academic self-efficacy. Also academic achievement was associated with having high academic self-efficacy.